Androgen-induced Long Noncoding RNA (lncRNA) SOCS2-AS1 Promotes Cell Growth and Inhibits Apoptosis in Prostate Cancer Cells - Misawa, Aya; Takayama, Ken-ichi; Urano, Tomohiko; Inoue, Satoshi (The Journal of biological chemistry, 2016)
Long noncoding RNAs (lncRNA) have been associated with the development of cancer. However, the interplay between lncRNAs and androgen receptor (AR) signaling in prostate cancer is still unclear. Here, we identified lncRNAs induced by androgen in AR-positive prostate cancer cells, where induction was abolished by AR knockdown as well as an anti-androgen, bicalutamide. By combining these data, we identified an androgen-regulated lncRNA, suppressor of cytokine signaling 2-antisense transcript 1 (SOCS2-AS1), the expression of which was higher in castration-resistant prostate cancer model cells, i.e. long-term androgen-deprived (LTAD) cells, than in parental androgen-dependent LNCaP cells. SOCS2-AS1 promoted castration-resistant and androgen-dependent cell growth. We found that SOCS2-AS1 knockdown up-regulated genes related to the apoptosis pathway, including tumor necrosis factor superfamily 10 (TNFSF10), and sensitized prostate cancer cells to docetaxel treatment. Moreover, we also demonstrated that SOCS2-AS1 promotes androgen signaling by modulating the epigenetic control for AR target genes including TNFSF10. These findings suggest that SOCS2-AS1 plays an important role in the development of castration-resistant prostate cancer by repressing apoptosis.